Immunotherapy in melanoma: advances, pitfalls, and future perspectives - Sorino, Cristina; Iezzi, Simona; Ciuffreda, Ludovica; Falcone, Italia (Frontiers in Molecular Biosciences, 2024)
Cutaneous melanoma is the most aggressive and deadly form of skin cancer due to its high capacity to metastasize. Over the last decades, the management of this malignancy has undergone a significant revolution with the advent of both target therapies and immunotherapy, which greatly improved patients' quality of life and survival. Nevertheless, the response rate is still unsatisfactory for the presence of side effects and the development of resistance mechanisms. In this context, tumour microenvironment has emerged as a factor affecting the responsiveness and efficacy of immunotherapy and the study of its interplay with the immune system is opening new promising clinical strategies. This review will provide a brief overview of the currently available immunotherapeutic strategies for melanoma treatment, analysing both the positive aspects but also the ones that require further improvement. Indeed, a better understanding of the mechanisms involved in immune evasion of melanoma cells, with particular attention on the role of tumor microenvironment, could provide the basis to improve current therapies and identify new predictive biomarkers. modified melanoma patient management and significantly improved long-term survival (11). Unfortunately, often this kind of treatment offers only a transient benefit to the patient and can also produce toxic effects (11,12). Thus, there is an urgent need to identify predictive biomarkers of response and new rational targets for more effective therapies, to overcome immune resistance and minimize toxic effects. This review will provide an update overview of recent immunotherapy advances and future perspectives for metastatic melanoma treatment.